Heilsgeographie - Geografia zbawienia. Zapoznana idea świętej przestrzeni - Mielcarek, Krzysztof (The Biblical Annals, 2015)
The article deals with the issue little discussed nowadays, for in comparison to a very popular idea of the history of salvation, biblical geography of salvation is rather neglected. There are of course some very good articles and monographs devoted to the role of the land within biblical tradition, but scholars tend to diminish the significance of the holy space within the Christian experience. However, even though the Holy Land is certainly a less significant factor in Christianity tradition than it is in the Old Testament and in the current Judaism, one cannot separate history from its cultural and geographical setting. Thus contemporary Christian experience must contain its spatial feature and it has to be consciously appreciated.